2023
DOI: 10.3390/ijms241814270
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalin as a Promising Anticancer Agent: Molecular Mechanisms and Future Perspectives for the Development of New Nanoformulations for Its Delivery

Maria Spanoudaki,
Sofia Stoumpou,
Sousana K. Papadopoulou
et al.

Abstract: Cancer rates are increasing, and cancer is one of the main causes of death worldwide. Amygdalin, also known as vitamin B17 (and laetrile, a synthetic compound), is a cyanogenic glycoside compound that is mainly found in the kernels and pulps of fruits. This compound has been proposed for decades as a promising naturally occurring substance which may provide anticancer effects. This is a comprehensive review which critically summarizes and scrutinizes the available studies exploring the anticancer effect of amy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…( Munekata et al, 2023 ). However, its positive bioactive effects include anti-inflammatory, antibacterial, antioxidant, and immunomodulatory effects( Barakat et al, 2022 ), as well as reported but unproven anticancer activity has also been widely reported ( Spanoudaki et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…( Munekata et al, 2023 ). However, its positive bioactive effects include anti-inflammatory, antibacterial, antioxidant, and immunomodulatory effects( Barakat et al, 2022 ), as well as reported but unproven anticancer activity has also been widely reported ( Spanoudaki et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%